2020
DOI: 10.1103/physrevmaterials.4.082602
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively consistent scale-spanning model for same-material tribocharging

Abstract: By rigorously accounting for mesoscale spatial correlations in donor/acceptor surface properties, we develop a scale-spanning model for same-material tribocharging. We find that mesoscale correlations affect not only the magnitude of charge transfer but also the fluctuations-suppressing otherwise overwhelming charge-transfer variability that is not observed experimentally. We furthermore propose a generic theoretical mechanism by which the mesoscale features might emerge, which is qualitatively consistent with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The measurements could be modeled with patches of charge on the surface of the particles. Irregularly charged surfaces are also consistent with the work by Grosjean et al (2020) and Apodaca et al (2010) on identical material charging. Strong interactions between charge patches should also influence a collision between two dielectric grains and their final approach to one another if these particles have a non-homogeneous charge distribution.…”
Section: Introductionsupporting
confidence: 79%
“…The measurements could be modeled with patches of charge on the surface of the particles. Irregularly charged surfaces are also consistent with the work by Grosjean et al (2020) and Apodaca et al (2010) on identical material charging. Strong interactions between charge patches should also influence a collision between two dielectric grains and their final approach to one another if these particles have a non-homogeneous charge distribution.…”
Section: Introductionsupporting
confidence: 79%
“…However, the agitation method and therefore the process of particle charging is almost identical to previous studies, either with glass beads (Jungmann et al 2018(Jungmann et al , 2021Steinpilz et al 2020a) or with basalt beads (Wurm et al 2019). The width (FWHM) of the corresponding charge distribution scales with the particle size (Wurm et al 2019), with many studies treating charges on insulators as surface charges only (Lee et al 2018;Grosjean et al 2020;Steinpilz et al 2020b). With a similar charge density on the surface as in Wurm et al (2019), a charge distribution centered at zero charge with a FWHM of about 3 • 10 −13 C can be expected.…”
Section: Chargesmentioning
confidence: 69%
“…A dimer or a more complex aggregate still hold charges on their surface. It has to be noted at this point that collisions lead to charge separation (not neutralization) in the first place and grains charged this way have a complex charge pattern with patches of negative and positive charges on their surface (Grosjean et al 2020;Steinpilz et al 2020b). This is also valid for grains which are net neutral.…”
Section: Charge Driven Aggregation and Stabilitymentioning
confidence: 94%
“…It was shown that, as long as charges are considered to be located in the center of the beads, neither the Coulomb force of randomly distributed net charges nor the electric field of a conducting plane can reproduce the observed values. Based on results of Jungmann et al (2018), Steinpilz et al (2020b) and Grosjean et al (2020) among others, we also applied a model of charged surface patches. We note that there is no detailed analysis of the surface charge pattern, i.e., the size of the patches and the charges incorporated in them.…”
Section: Discussion and Application To Marsmentioning
confidence: 99%